GROUNDSTROKE TRAINING MODEL BASED ON SITUATION GAME FOR FIELD TENNIS ATHLETES AGED 12-14 YEARS - Divya Zuhra; Junaidi; Nofi Marlina Siregar (Gladi : Jurnal Ilmu Keolahragaan, 2022)
This study aims to create a game situation-based groundstroke forehand and groundstroke backhand training model for tennis athletes aged 12-14 years and improve forehand and backhand skills using a game situation-based groundstroke training model for athletes aged 12-14 years. The research method used is the Research & Development Research & Development (R&D) Borg and Gall method. Subjects studied were 15 people and were athletes aged 12-14 years. The results of the pre-test test obtained an average of 31.73. Then, the post-test obtained an average of 40.00. The exercise correlation coefficient before and after the exercise model was given was 0.946 with a p-value of 0.00 < 0.05, so the conclusion was significant. In the mean difference test with SPSS, the mean = 8.26667 shows the difference between the pre-test and post-test, the result of t-count = 26,183, df = 19 and p-value = 0.00<0.05, which means there is a significant difference between before and after being given game situation based groundstroke training model treatment. Based on these results, it can be concluded that the game situation-based groundstroke training model for tennis athletes at the age of 12-14 years is effective and can improve the forehand groundstroke.